Psychological diagnosis in primary glaucoma: analysis of the types of attitudes of gerontological patients to the disease - S. I. Makogon; A. L. Onishchenko; A. S. Makogon (Офтальмохирургия, 2020)
Purpose. To study the type of relationship to the disease in patients with primary open-angle glaucoma of different age groups.Material and methods. The study involved 312 patients with primary open-angle glaucoma of the stages I –IV who were treated at the Regional Ophthalmological Hospital. The patients were divided into 3 groups: the group 1 had 104 patients of middle age (45–59 years old), of them: 44 male (42.3%) and 60 female (57.7%), the group 2 – 110 elderly people (60–74 years) of them: 46 male (41.8%) and 64 female (58.2%), the group 3 – 98 elderly patients (75 years and older) – 36 male (36.7%) and 62 female (63.3%). For a psychological diagnosis of types of attitude towards the disease, the ≪TOBOL≫ method was used.Results. Among the middle-aged patients, a harmonious and ergopathic type of attitude to the disease prevailed (21.95% and 20.14%, respectively) as well as a moderately pronounced sensitive type (11.23%). Among the elderly patients, a significant decrease was noted in indicators of a harmonious type of attitude to the disease, compared with the middle-aged patients (average indicators on a scale of harmony: 21.95±0.69 vs. 12.65±0.66; p≤0.05). Both males and females of advanced age were characterized by a high degree manifestation of anxious, hypochondriac, sensitive tendencies, with moderately pronounced neurasthenic and melancholic tendencies. Among the patients of senile age, a decrease in the harmonious type of attitude to the disease, a severity of hypochondriac and neurasthenic tendencies were also detected compared with the middle-aged patients.Conclusion. A comparative analysis of the types of attitude to the disease in patients with primary open-angle glaucoma of different age groups showed significant differences between individuals of the elderly and senile age compared with middle-aged people.